2008
DOI: 10.1183/09031936.00114807
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor swimming pools and the risks of asthma and allergies during adolescence

Abstract: Exposure to indoor chlorinated swimming pools can be detrimental to the airways of swimmers and increase asthma risks but it is unknown whether these effects concern outdoor pools.The present study examined 847 secondary school adolescents who had attended residential or nonresidential outdoor chlorinated pools at a variable rate. The main outcomes were: ever asthma (physician-diagnosed at any time); current asthma (ever asthma under medication and/or with exercise-induced bronchoconstriction); elevated exhale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 32 publications
1
53
0
1
Order By: Relevance
“…Furthermore, they attend smaller, hotter, and eventually more polluted swimming pools than adults. Studies conducted in Belgium reported an increased risk of asthma among children with atopy that was associated with early indoor [87][88][89] and outdoor [90] swimming pool attendance. However, studies in other European countries such as Germany [91], Spain [92,93], the UK [94•], and the Netherlands [95], have found no association between swimming pool attendance and respiratory symptoms among children.…”
Section: Childrenmentioning
confidence: 99%
“…Furthermore, they attend smaller, hotter, and eventually more polluted swimming pools than adults. Studies conducted in Belgium reported an increased risk of asthma among children with atopy that was associated with early indoor [87][88][89] and outdoor [90] swimming pool attendance. However, studies in other European countries such as Germany [91], Spain [92,93], the UK [94•], and the Netherlands [95], have found no association between swimming pool attendance and respiratory symptoms among children.…”
Section: Childrenmentioning
confidence: 99%
“…Likewise, the authors have recently reported an association between outdoor swimming pool attendance and the risk of asthma, airway inflammation and sensitization to some indoor allergens. 42 The authors therefore hypothesized that regular attendance at chlorinated swimming pools might have a role in the development of asthma by causing an increased lung permeability, which could in turn facilitate allergen sensitization. 1 In another study, the same group demonstrated a linear relationship between asthma prevalence and cumulated pool attendance only in children with total IgE > 100 kU/L, supporting the hypothesis that the relationship between asthma and cumulated pool attendance might be due mostly to interaction with atopic status.…”
Section: Respiratory Effects Of Chronic Chlorine Exposure In Nonasthmmentioning
confidence: 99%
“…However, health effects in recreational visitors and especially in children are more controversial. One study found higher risks of developing asthma and airway inflammation, when adolescents attended outdoor swimming pools [49]. Several studies also indicate that young children who often visit indoor swimming pool facilities have a higher risk of developing respiratory problems such as asthma, increased lung epithelium permeability, recurrent bronchitis and allergy, later in childhood [50][51].…”
Section: Swimming Pool Facilitiesmentioning
confidence: 99%